Strategic Ambivalence: How British Evangelical Women Navigate Male Headship - Tolson, Hannah (Religion & gender, 2025)
Contributing to scholarship on gender in Evangelical Christianity, this article focuses on the notion of male headship. With existing literature concerned with male headship within the marital sphere, this study also investigates beliefs about male headship in church settings, and the interconnections between these two topics. Interviews with ten British, Evangelical women were conducted on male headship, gender roles, and gender discrimination in church. This study found that participants generally affirmed male headship within the marital and familial sphere, showing ambivalence towards male headship in the church. This ambivalence helps participants stay in churches which bar women from church governing roles, despite participants expressing support for women in church leadership.